Incarnation: the history and mysticism of the tulku tradition of Tibet - Tulku Thondup (Colorado : Shambhala, 2016)
A tulku is a fully enlightened one (buddha) or highly accomplished adept (siddha) who chooses to be reborn again and again for the benefit of all beings. Most tulkus, though, are the rebirths of well-trained masters who are engaged in spiritual training and serving others. Tibetan Buddhists have, for well over a millennium, been meticulously following the tradition of finding, recognizing, enthroning, training, and venerating these revered figures who provide teachings of liberation for both monks and laypeople. This guide to the tulku tradition covers its long history, separating fact from fiction, giving an overview of how the system works, and providing short biographies of some of the great tulkus of the past and present. Included are accounts of the magical occurrences that are associated with these remarkable beings, and advice for how anyone can set out on the tulku path.
Includes bibliographical and indes.
Keywords: Reincarnate lamas -- China | -- Tibet Autonomous Region; Reincarnation -- Buddhism